Investigation on CEED-RES Problem Using Modified Lagrange Method - Manikandan, K.; Sasikumar, S.; Arulraj, R. (Distributed Generation & Alternative Energy Journal, 2022)
The notion of a micro grid system is used to prevent transmission losses and to ensure a dependable power supply to a limited geographical area. It has been a mandatory protocol to apply accessible Renewable Energy Sources (RES) in order to reduce hazardous pollutants released into the atmosphere as a result of fossil fuel burning. Economic load dispatch (ELD) is concerned with the most cost-effective sizing of distributed energy resources (DERs). By limiting the hazardous content of pollutants emitted into the atmosphere, emission dispatch determines the ideal size of DERs. A multi-objective Combined Economic-Emission Dispatch (CEED) is created, which determines the appropriate DER sizing while minimizing both fuel costs and pollution emissions. Using Python programming in IDLE, this work conducts all ELD, Emission Dispatch, and CEED on a renewable-integrated micro grid and grid connected mode independently. The results are then compared with conventional method effectiveness of the proposed technique. In this paper, the algorithm proposed in python language to check the accuracy, multidisciplinary integration and ease of understanding. This article is developed based on conventional CEED solution and validated with the help of Python programming for a typical IEEE test system.